STRATEGY TO PROMOTE PATIENT CENTERED CARE PCC FOR IMPROVING PATIENT SATISFACTION: A LITERATURE REVIEW - Wahyuni; Mira Triharini; Eka Mishbahatul Mar’ah Has (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: Patient satisfaction is playing an increasingly important role in care-quality reforms and healthcare delivery in general. Patient dissatisfaction with nursing services was still a problem in Indonesia and in other developing countries. Patient Centered Care (PCC) as one of the six dimensions of improving the quality of care. Objectives: The purpose of this study aimed to analyse Strategy to Promote PCC for Improving Patient Satisfaction. Design: This study using systematic review design refers to The Center for Review and Dissemination and the Joanna Briggs Institute Guideline. Data Sources: Search for articles was conducted from 14 December 2020 to 28 April 2021 by accessing four electronic databases (Scopus, PubMed, ProQuest, Sage). The article year is limited from 2015-2021. Keywords: “Strategy” OR “Promote” OR “Intervention” AND “Patient Centred Care” OR “Patient Care Management” AND “Patient Satisfaction” OR “Patient Acceptance”. Review Methods: Assessing the quality of articles using the JBI Critical Appraisal Tool and PRISMA checklist as a guide in article screening. Results: A total of 15 article were analyzed according to inclusion criteria. The selected article is divided in five broad themes about strategy to promote patient centered care. The five broad themes are enhanced communication (n=4), promoting patient participation (n=4), emotional support (n=2), intervention to enhanced patient centered care (n=3) and organizational culture (n=2). Conclusion: There are 5 strategies to promote patient centered care for improving patient satisfaction. Five patient centered care strategies to improve patient satisfaction involve enhance communication, promoting patient participation, emotional support, intervention to enhanced patient centered care and organizational culture.